Cortical nNOS neurons co-express the NK1 receptor and are depolarized by Substance P in multiple mammalian species - Dittrich, Lars; Heiss, Jaime E.; Warrier, Deepti R.; Perez, Xiomara A.; Quik, Maryka; Kilduff, Thomas S. (Frontiers in Neural Circuits, 2012)
We have previously demonstrated that Type I neuronal Nitric Oxide Synthase (nNOS)-expressing neurons are sleep-active in the cortex of mice, rats and hamsters. These neurons are known to be GABAergic, to express Neuropeptide Y and, in rats, to co-express the Substance P (SP) receptor NK1, suggesting a possible role for SP in sleep/wake regulation. To evaluate the degree of co-expression of nNOS and NK1 in the cortex among mammals, we used double immunofluorescence for nNOS and NK1 and determined the anatomical distribution in mouse, rat, and squirrel monkey cortex. Type I nNOS neurons co-expressed NK1 in all three species although the anatomical distribution within the cortex was species-specific. We then performed in vitro patch clamp recordings in cortical neurons in mouse and rat slices using the SP conjugate tetramethylrhodamine-SP (TMR-SP) to identify NK1-expressing cells and evaluated the effects of SP on these neurons. Bath application of SP (0.03-1 µM) resulted in a sustained increase in firing rate of these neurons; depolarization persisted in the presence of tetrodotoxin. These results suggest a conserved role for SP in the regulation of cortical sleep-active neurons in mammals.